Combination therapy of ofatumumab and daratumumab in patients with severe anti-NMDA receptor encephalitis - Wang, Baojie; Chu, Yufeng; Zhang, Chao; Guo, Shougang (Frontiers in Immunology, 2025)
N-methyl-D-aspartate receptor (NMDAR) antibody encephalitis (NMDARE) is an autoimmune disorder in which approximately 25% of patients develop refractory disease with severe prolonged neurological deficits. Currently, there is no consensus on optimal treatment for NMDARE refractory to first- or second-line therapies. We present two cases of severe refractory NMDARE treated with novel combination therapy of ofatumumab and daratumumab. We describe two adolescent female patients with severe neuropsychiatric manifestations unresponsive to standard first-line therapies, including intravenous methylprednisolone (IVMP) and intravenous immunoglobulins (IVIG). Following 5–6 cycles of ofatumumab and daratumumab combination therapy, both patients achieved significant functional improvement (modified Rankin Scale [mRS] score ≤ 2) within 12 weeks. Serological analysis revealed undetectable NMDAR-IgG levels and rapid depletion of circulating CD19+ B cells and CD38+ antibody-secreting cells (ASCs) within 2 weeks. Treatment-related adverse events were acceptable. This case report demonstrates that combined treatment of ofatumumab and daratumumab therapy is well-tolerated and may represent a novel therapeutic strategy for severe NMDARE. The observed rapid serological and clinical responses highlight its potential efficacy, warranting further investigation in large cohorts.